The Effectiveness of Mindful Parenting in Reducing Stress Levels among Young Mothers of Preschool-Age Children - Harvi Wahyu Putriadi; Djudiyah Djudiyah (International Journal of Social Sciences, Language, and Education, 2026)
This empirical study evaluates the structural efficacy of a targeted mindful parenting training program in mitigating chronic caregiving stress among young mothers rearing preschool age children between three and six years old. Utilizing a quantitative approach embedded within a single group pretest posttest quasi experimental research framework, a homogeneous cohort of thirty active participants underwent a four week structured curriculum focused on introspective emotional awareness, somatic relaxation, attentive listening, and non judgmental acceptance. Longitudinal psychometric data collection executed via the locally adapted Parenting Stress Scale demonstrated a highly significant, uniform reduction in macro level parenting distress, with mean aggregate stress metrics dropping from 48.40 at baseline to 32.50 post intervention (). Advanced domain analysis confirms that the intervention operates via dual mechanisms, simultaneously reducing immediate reactive emotional outbursts within the personal stressor domain and enhancing maternal efficacy and socio contextual adaptability against macro environmental pressures such as economic instability, digital sleep disruptions, and pediatric hospitalization anxiety. These findings establish mindful caregiving as a vital clinical asset that permanently neutralizes maladaptive disciplinary practices and fosters optimal early childhood social emotional development.